Round Trip to Hades in the Eastern Mediterranean Tradition, Visits to the Underworld from Antiquity to Byzantium. - Gunnel Ekroth; Ingela Nilsson (Volume Editors) (Cultural Interactions in the Mediterranean, 2018)
Round Trip to Hades in the Eastern Mediterranean Tradition explores how the theme of visiting the Underworld and returning alive has been treated, transmitted and transformed in the ancient Greek and Byzantine traditions. The journey was usually a descent ( katabasis ) into a dark and dull place, where forgetfulness and punishment reigned, but since 'everyone' was there, it was also a place that offered opportunities to meet people and socialize. Famous Classical round trips to Hades include those undertaken by Odysseus and Aeneas, but this pagan topic also caught the interest of Christian writers. The contributions of the present volume allow the reader to follow the passage from pagan to Christian representations of Hades-a passage that may seem surprisingly effortless.